1988
DOI: 10.1073/pnas.85.7.2135
|View full text |Cite
|
Sign up to set email alerts
|

The alpha and beta chains of human platelet glycoprotein Ib are both transmembrane proteins containing a leucine-rich amino acid sequence.

Abstract: The primary structure of the (3 chain of human glycoprotein lb (GPIb), the platelet receptor for von Willebrand factor, has been established by a combination of cDNA cloning and amino acid sequence analysis. A A phage cDNA expression library prepared from human erythroleukemia cells (HEL cells) was screened with a radiolabeled affinitypurified rabbit polyclonal antibody to the ( chain of GPIb. Eighteen positive clones were isolated and plaque-purifiled and the nucleotide sequences of three were determined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(89 citation statements)
references
References 40 publications
0
88
0
Order By: Relevance
“…This clustering of mutations prompted us to examine the carboxy-terminal flanking sequences of other L-rich repeat-containing proteins more closely. In Toil, both blocks of L-rich repeats are followed by a cysteine-containing motif, which is also found in a subset of proteins that have extracellular Lrich repeats including L-rich glycoprotein {Takahashi et al 1985}, the platelet transmembrane proteins gp lb and 13, gp IX (Lopez et al 1987(Lopez et al , 1988Hickey et al 1989}, and the lutropin-choriogonadotropin receptor (McFarland et al 1989}. We found that the similarity between these motifs extends further than described previously {Hickey et Keith and Gay 1990} and that the motifs contain four, rather than only two, conserved cysteine residues {Fig.…”
Section: Two Classes Of Dominant Alleles Of Toll Change the Extracellmentioning
confidence: 99%
See 1 more Smart Citation
“…This clustering of mutations prompted us to examine the carboxy-terminal flanking sequences of other L-rich repeat-containing proteins more closely. In Toil, both blocks of L-rich repeats are followed by a cysteine-containing motif, which is also found in a subset of proteins that have extracellular Lrich repeats including L-rich glycoprotein {Takahashi et al 1985}, the platelet transmembrane proteins gp lb and 13, gp IX (Lopez et al 1987(Lopez et al , 1988Hickey et al 1989}, and the lutropin-choriogonadotropin receptor (McFarland et al 1989}. We found that the similarity between these motifs extends further than described previously {Hickey et Keith and Gay 1990} and that the motifs contain four, rather than only two, conserved cysteine residues {Fig.…”
Section: Two Classes Of Dominant Alleles Of Toll Change the Extracellmentioning
confidence: 99%
“…The 803-amino acid residue extracellular domain, of Toll is composed largely of two blocks of leucine-rich (L-rich) repeats. L-rich repeats of this type have been found in a diverse group of proteins including the transmembrane protein platelet protein glycoprotein (gp) lb ~ and f3, gp IX, and the lutropinchoriogonadotropin receptor (Lopez et al 1987(Lopez et al , 1988Hickey et al 1989;McFarland et al 1989). The Drosophila protein chaoptin, which is composed almost exclusively of L-rich repeats, can mediate homotypic cell adhesion (Krantz and Zipursky 1990), and Toll itself can promote heterotypic cell adhesion (Keith and Gay 1990), providing evidence that this motif defines a protein-protein interaction domain.…”
mentioning
confidence: 99%
“…The 145 kD GPIba contains von Willebrand factor (VWF) and thrombin binding sites and is linked to the 27 kD GPIbb by a disulphide bond. The 22 kD GPIX is noncovalently bound and GPV is more weakly associated (Lopez et al, 1987(Lopez et al, , 1988Hickey et al, 1989;Modderman et al, 1992).…”
mentioning
confidence: 99%
“…Von Willebrand factor acts as a bridge between the platelets and the injury site [ 62 , 63 ] as it binds to specific receptors, namely glycogprotein Ib/glycoprotein IX, on the surface of activated platelets as well as the subendothelium [ 64 ]. Similarly, fibrinogen also acts a platelet-platelet bridge as it binds to the surface receptors glycoprotein IIb/IIIa on adjoining activated platelets [ 65 , 66 ].…”
Section: Platelets Fibrin Network and Clotting Factors Plateletsmentioning
confidence: 99%